2022
DOI: 10.1038/s41398-022-02195-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation as a potential mediator of the association between prenatal tobacco and alcohol exposure and child neurodevelopment in a South African birth cohort

Abstract: Prenatal tobacco exposure (PTE) and prenatal alcohol exposure (PAE) have been associated with an increased risk of delayed neurodevelopment in children as well as differential newborn DNA methylation (DNAm). However, the biological mechanisms connecting PTE and PAE, DNAm, and neurodevelopment are largely unknown. Here we aim to determine whether differential DNAm mediates the association between PTE and PAE and neurodevelopment at 6 (N = 112) and 24 months (N = 184) in children from the South African Drakenste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…Finally, we aimed to test whether DNA methylation mediated the pathway between prenatal risk and cognitive ability, using a combination of high-dimensional and causal mediation analyses. In line with emerging evidence (Abrishamcar et al, 2022;Feil et al, 2023), we hypothesized that we would find significant mediated pathways through one or more CpG site(s).…”
Section: The Current Studymentioning
confidence: 84%
See 4 more Smart Citations
“…Finally, we aimed to test whether DNA methylation mediated the pathway between prenatal risk and cognitive ability, using a combination of high-dimensional and causal mediation analyses. In line with emerging evidence (Abrishamcar et al, 2022;Feil et al, 2023), we hypothesized that we would find significant mediated pathways through one or more CpG site(s).…”
Section: The Current Studymentioning
confidence: 84%
“…The majority of studies examining epigenetics as a mediator of environmental risk have used candidate gene approaches (for a review, see Barker et al, 2018). Two recent studies used HDMA to test whether DNA methylation mediated the associations between prenatal tobacco and alcohol exposure (Abrishamcar et al, 2022) and indoor air pollution (Feil et al, 2023) and child neurodevelopmental outcomes in a South African birth cohort. Similar to our findings, both prior studies identified significant epigenetic mediators, but only with the DACT (as opposed to HIMA) approaches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations